Evaluation of Haematocrit, Haemoglobin Level and EPO mRNA Expression among Male Blood Donors in Ibadan, South-West Nigeria (Sahel Journal of Life Sciences FUDMA, 2025)
Evaluating erythropoietin (EPO) mRNA expression alongside conventional haematologic indices offers deeper insight into the body’s compensatory erythropoietic response. While most studies on blood donors focus on haemoglobin (Hb) and haematocrit (Hct), little is known about EPO gene expression, particularly among male donors who constitute the majority in many regions. This cross-sectional study assessed Hct, Hb, and EPO mRNA expression in 100 male donors in Ibadan, Nigeria (50 regular, 50 occasional). Haematological parameters were measured using automated methods, while EPO mRNA was quantified by GAPDH-normalised RT-PCR. Data were analysed using independent t-tests, Pearson’s correlation, and Mann–Whitney U tests at p